2009
DOI: 10.1111/j.1365-2141.2008.07487.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up analysis after rituximab therapy in children with refractory symptomatic ITP: identification of factors predictive of a sustained response

Abstract: Summary We report the long‐term follow‐up (median 39·5 months) of 49 paediatric patients (33 females and 16 males) with refractory symptomatic immune thrombocytopenic purpura (ITP) treated with rituximab. The overall response rate was 69% (34/49 patients). Twenty‐one responders had a platelet count >50 × 109/l at a median 20·2 months from treatment. Kaplan–Meier analysis showed a probability of relapse‐free survival (RFS) of 60% at 36 months from the first rituximab infusion. The number of infusions and a prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
68
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 24 publications
5
68
0
6
Order By: Relevance
“…In the 1-year follow-up of a prospective, multicenter trial of 4 weekly doses of rituximab (375 mg/m 2 ) 35 only 8 of 36 patients maintained their platelet counts above 50 ϫ 10 9 /L. 36 Higher response rates were found in some other trials [37][38][39][40] including one that allowed doubling of the dose if there was no response to the initial therapy. 39 Serum sickness has occurred in some patients 35,37,39 and the rate of more significant long-term adverse events such as progressive multifocal leukoencephalopathy remains uncertain.…”
Section: 3b We Suggestmentioning
confidence: 99%
“…In the 1-year follow-up of a prospective, multicenter trial of 4 weekly doses of rituximab (375 mg/m 2 ) 35 only 8 of 36 patients maintained their platelet counts above 50 ϫ 10 9 /L. 36 Higher response rates were found in some other trials [37][38][39][40] including one that allowed doubling of the dose if there was no response to the initial therapy. 39 Serum sickness has occurred in some patients 35,37,39 and the rate of more significant long-term adverse events such as progressive multifocal leukoencephalopathy remains uncertain.…”
Section: 3b We Suggestmentioning
confidence: 99%
“…The overall response rates, complete and partial, to initial treatment with rituximab (375 mg/m 2 ϫ 4) in adults and children with ITP were both 57% (Table 1). Two times as many responses in adults, as defined in the original reports, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][27][28][29] were complete responses (CR: platelet count Ͼ 150 ϫ 10 9 /L, 38%) as opposed to partial responses (PR: platelet count 50-150 ϫ 10 9 /L, 19%). In the 2 studies that assessed duration of effect according to type of initial response, patients achieving CRs had a greatly increased likelihood of maintaining their response at least 1 year from initial treatment compared with patients who achieved PRs.…”
mentioning
confidence: 99%
“…In the 2 studies that assessed duration of effect according to type of initial response, patients achieving CRs had a greatly increased likelihood of maintaining their response at least 1 year from initial treatment compared with patients who achieved PRs. 6,27 Four studies 16,18,27,30 (Table 1) preliminarily assessed the durability of response in patients with ITP. The largest study, with 60 initially treated adults, reported a 43% 1-year response rate and a 40% 2-year response rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, considering the B cell-selective pharmacological effects and the limited side effects of rituximab, this therapy might be particularly useful in young anti-NMDAR encephalitis patients without tumor lesions (2,5,7,13,14,20,(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%